Pemberdayaan Kelompok Pemuda melalui Pelatihan Desain Packaging Kemasan Produk Premium UMKM Binaan Mahasiswa KKN STAI Muhammadiyah Blora - Sholihul Anwar; Mohamad Munawar; Dian Ari Anjarjati; Mohammad Tulus Widodo (Bulletin of Community Engagement, 2025)
This community service activity aims to empower youth-led MSME (Micro, Small, and Medium Enterprises) groups in Todanan Village, Blora Regency, through training in premium product packaging design that aligns with current digital market trends. The initiative was driven by the low competitiveness of local MSME products, often caused by unprofessional packaging design and limited youth awareness of the importance of product visualization in enhancing market value. The training was conducted collaboratively by lecturers and students from the Community Service Program (KKN) of STAI Muhammadiyah Blora, in partnership with BLKK PD Muhammadiyah Blora, using a participatory approach involving observation, interviews, hands-on training, and technical assistance. The training materials covered the basics of graphic design, logo and label creation, as well as product marketing strategies through social media and e-commerce platforms such as Shopee. The results show that participants successfully produced more appealing and functional packaging designs and began marketing their products digitally. This training significantly enhanced the participants’ design creativity, product branding understanding, and strengthened the role of youth in promoting local economic growth through MSME development. This program contributes to the development of practical design and digital marketing skills among rural youth, offering a replicable model for community empowerment through creative economy initiatives. It also demonstrates how academic institutions can play a vital role in bridging knowledge and skill gaps within local entrepreneurial ecosystems.